Peran Mediasi Customer Engagement Pada Analisis Pengaruh Gamifikasi Digital, Percieved Personalization, Dan Algoritma Plaform Terhadap Impulse Buying Konsumen Generasi Z Di E-Commerce Shopee - Ilham Rizki Maulana; Muhammad Ridwan Basalamah; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract The rapid growth of e-commerce has significantly influenced consumer behavior, particularly among Generation Z, who are increasingly prone to impulse buying. Shopee, as one of the largest e-commerce platforms in Indonesia, implements various digital strategies such as digital gamification, perceived personalization, and platform algorithms to enhance user experience. This study aims to analyze the effects of digital gamification, perceived personalization, and platform algorithms on impulse buying among Generation Z consumers on Shopee, as well as to examine the mediating role of customer engagement. This research employs a quantitative approach using a survey method involving Generation Z consumers who are active Shopee users. The sampling technique used is purposive sampling, and the data are analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. The results indicate that digital gamification, perceived personalization, and platform algorithms have a positive and significant effect on impulse buying. Furthermore, these three variables also have a positive and significant effect on customer engagement. Customer engagement is found to have a positive and significant effect on impulse buying and is able to mediate the effects of perceived personalization and platform algorithms on impulse buying. This study concludes that customer engagement plays a crucial role in explaining how digital strategies implemented by e-commerce platforms can stimulate impulse buying behavior among Generation Z consumers. Keywords: Digital Gamification, Perceived Personalization, Platform Algorithms, Customer Engagement, Impulse Buying.